2022
DOI: 10.1002/smi.3135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nature‐based physical activity on post‐traumatic growth among healthcare providers with post‐traumatic stress

Abstract: The purpose of this randomized control trial was to observe the effect of naturebased physical activity in achieving post traumatic growth and to estimate the combined effect of nature and physical activity on the psychophysiological outcomes. A 3-month therapy was provided to participants meeting eligibility criteria to receive the walk-in nature (experimental group) or sit-in nature (control group) in the 1:1 ratio. At baseline and 3-month follow-up, participants were assessed with Trauma Symptom Checklist 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Researchers of several experimental studies have measured changes in cortisol before and after spending time in nature. Several studies have reported significant decreases in cortisol after participants spent time in nature [ 158 , 177 , 226 , 227 , 228 ]. Furthermore, Hunter et al was able to estimate how much time in nature is needed to decrease cortisol; reporting that intentionally interacting with nature for 20–30 min resulted in an 18.5% decrease in cortisol per hour [ 229 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers of several experimental studies have measured changes in cortisol before and after spending time in nature. Several studies have reported significant decreases in cortisol after participants spent time in nature [ 158 , 177 , 226 , 227 , 228 ]. Furthermore, Hunter et al was able to estimate how much time in nature is needed to decrease cortisol; reporting that intentionally interacting with nature for 20–30 min resulted in an 18.5% decrease in cortisol per hour [ 229 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additional intervention research studies have reported improvements in parasympathetic nervous system activity [ 170 , 171 , 172 , 173 , 232 ], heart rate variability [ 233 ], heart rate recovery [ 234 ], and general health [ 23 , 235 ]; and reductions in sympathetic nervous system activity [ 170 , 171 , 172 , 236 ], heart rate [ 170 , 171 , 172 , 184 , 232 , 237 , 238 , 239 ], overall blood pressure [ 184 ], systolic blood pressure [ 162 , 171 , 179 , 227 , 234 , 237 , 238 ], diastolic blood pressure [ 162 , 179 , 227 , 234 ], cardiac function [ 237 ], vascular function [ 237 ], mean arterial pressure [ 162 ], pulse pressure [ 237 ], C-reactive protein [ 226 ], interleukin 6 [ 226 ], gastrointestinal symptoms [ 240 ], and pain [ 235 ]. Researchers have also shown that, after interventions that utilize intentional interactions with nature, there are significant increases in brain-derived neurotrophic factor [ 195 , 241 ] and platelet-derived growth factor [ 241 ], which are related to memory.…”
Section: Resultsmentioning
confidence: 99%
“…The included articles were from Austria [ 41 , 43 ], The Netherlands [ 50 ], Spain [ 45 , 48 ], UK [ 42 ], Japan [ 49 ], China [ 51 ], Pakistan [ 47 ], Canada [ 52 ], USA [ 46 ] and South Korea [ 44 ], published between 2015 and 2022. One was a qualitative study [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…One on-going study identified at clinicaltrials.gov. The rest were peer-reviewed interventional effect studies: randomized controlled trials with two arms ( n = 5) [ 45 , 47 , 48 , 51 , 52 ] and three arms [ 43 ], a randomized cross-over group pilot trial [ 46 ], a comparative intervention study without randomization [ 44 ], a quasi-experimental design with a control group, no randomization [ 50 ] and two within subject experimental studies [ 41 , 49 ], with large variation in the number of included participants (range 19–262, median: 50) (see Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation